Effectiveness of a precast adjustable compression system compared to multilayered compression bandages in the treatment of breast cancer-related lymphoedema: a randomized, single-blind clinical trial - Pujol-Blaya, Vicenta; Salinas-Huertas, Sira; Catasús, M Luisa; Pascual, Teresa; Belmonte, Roser (Clinical rehabilitation, 2019)
To compare the effectiveness of a precast adjustable compression system with that of multilayered compression bandages in the treatment of breast cancer-related lymphoedema. Multicenter, randomized, single-blind parallel-group clinical trial. The rehabilitation services of four general university hospitals. Patients with upper limb breast cancer-related lymphoedema. All the patients received manual lymphatic drainage, followed by a precast adjustable compression system or multilayered compression bandages, according to the group allocation. The treatment included 10 consecutive sessions over a two-week period from Monday to Friday, followed by some sessions on three alternate days per week, until the patient received a tailored compression garment. The patients were evaluated just before the treatment, after 10 sessions and at three months posttreatment. The primary outcome was the change in excess lymphoedema volume. Secondary outcomes were changes in the symptoms of pain, heaviness, tightness and hardness. Analyses were performed using an intention-to-treat approach. In all, 42 patients were included; there were 22 in the precast adjustable compression system group and 20 in the multilayered compression bandages group. Both groups exhibited significant decreases in excess volume and symptoms after 10 sessions and at three months. There were no significant differences regarding excess volume or symptoms between the precast adjustable compression system and multilayered compression bandages groups after 10 sessions and at the three-month follow-up exam. The precast adjustable compression system and the multilayered compression bandages have similar efficacy for the reduction of excess lymphoedema volume or symptoms.